The revolution of robotic surgery in latin america and the future implementation in the healthcare system of Peru: La revolución de la cirugía robótica en latino américa y la futura implementación en el sistema de salud del perú - Cornejo-Aguilar, Jorge A. (2019)
Surgery has marked a milestone in history, from its origins and for many centuries, this specialty a close relationship with the healing of wounded in combat case presented during the beginning of Open Surgery, with the so-called Trepanaciones Craniaas that were made in the 700 a.C. - 200 AD for the Paracas Culture in Peru; with the During the time the techniques that were complemented with the use were perfected of new instruments and the development of technology leading to a revolution in the various Surgical specialties   DOI 10.25176/RFMH.v19.n1.1800